The Analysis of Formal Equivalence and Dynamic Equivalence in Translated Subtitle in Little Women Movie - SUDIANSYAH - (MEDIOVA: Journal of Islamic Media Studies, 2021)
This study aims to analyze the equivalence meaning of cultural words translation in Little Women movie subtitle. This study uses the theory of cultural words by Peter Newmark to analyze the type of cultural words and uses the theory from Nida to analyze the type of equivalence in translation. The methodology of this study is descriptive qualitative to give an explanation in analyzed the data. This study found data that categorized as cultural words which divided into two categorize of equivalence which are formal equivalence and dynamic equivalence. From the analysis, this study did not found the dynamic equivalence to ecology. The cultural words of formal equivalence translation is translated by using term that exist in target language and has the same meaning to the source language. The cultural words of dynamic equivalence translation is translated by using natural expression in target language that equal to the meaning in source language.